Determinants of gross domestic savings in Uganda: An autoregressive distributed lag (ARDL) approach to cointegration - Vivian Nagawa; Francis Wasswa; Edward Bbaale (Journal of Economic Structures, 2020)
In Uganda's development aspiration "VISION 2040", Uganda aspires to transform its society from a peasant to a modern and prosperous middle-income country by 2040, with per capita income of USD 9, 567. To attain the vision, savings as a percentage of GDP should be over 35%. Notwithstanding such a high commitment, GDS as a percentage of GDP has remained below the desired target, standing at 16.5% in 2017. This paper investigated the determinants of Gross Domestic Savings (GDS) in Uganda for the period 1980-2017. The theoretical framework is based on the life-cycle/permanent-income hypothesis. Augmented Dickey Fuller and Phillips-Perron tests were utilized to test for the stationarity of the time series variables in the model. To test for both the short-run and long-run relationships among GDS and the independent variables, the ARDL bounds testing approach was adopted. The observational results indicate that in the long run, Gross Domestic Product growth rate (GDPg), Foreign Domestic Investments (FDI) and Broad money (M2) have positive and statistically significant effects on GDS, while Current Account Balance (CAB) and Gross National Expenditure (GNE) have negative impacts on savings. Deposit Interest Rate (DIR) was observed to be a statistically unimportant determinant of GDS in Uganda. In the short run, CAB has a positive and statistically significant impact on GDS while GDPg and DIR have a negative and statistically significant impact on GDS. The paper recommends increasing net exports through implementation of the industrial and export strategy espoused in the national development plan 2. In addition, the government should ensure a predictable economic environment to act as an assurance to the foreign investors that their investments will yield profits.
Keywords: 330; Autoregressive distributed lag (ARDL); Cointegration; Error-correction model; Gross domestic savings (GDS); Life-cycle/permanent-income theory